Strong coast–ocean and surface–depth gradients in prokaryotic assemblage structure and activity in a coastal transition zone region - Baltar, Federico; Arístegui, Javier; Gasol, Josep M.; Hernández León, Santiago; Herndl, Gerhard J. (Aquatic Microbial Ecology, 2007)
12 pages, 5 figures, 1 table The distribution of marine Crenarchaeota Group I, marine Euryarchaeota Group II and some major groups of Bacteria (SAR 11, Roseobacter, Gammaproteobacteria and Bacteroidetes) was investigated in the North Atlantic water column (surface to 2000 m depth) along a transect from the coastal waters of the NW African upwelling to the offshore waters of the Canary Coastal Transition Zone (CTZ). Catalyzed reporter deposition-fluorescence in situ hybridization (CARD-FISH) was used to describe the prokaryotic assemblages. Bulk picoplankton abundance and leucine incorporation were determined. Pronounced changes in prokaryotic assemblage composition were observed from the coast to the open ocean and at the deep chlorophyll maximum (DCM) with decreasing bulk heterotrophic activity. All bacterial groups decreased in absolute abundances from the coast to the open ocean; both archaeal groups increased towards the open ocean. Prokaryotic abundance and activity decreased 2 and 3 orders of magnitude, respectively, from the surface to 2000 m. Prokaryotic growth rates were high in the mesopelagic zone (∼0.13 d-1), compared to other reports from the central North Atlantic. SAR11 in total picoplankton abundance decreased from 42 % in the DCM to 4 % at 2000 m, while marine Crenarchaeota Group I increased from 1 % in the DCM to 39 % in the oxygen minimum layer. A clear influence of the different intermediate water masses was observed on the bulk heterotrophic picoplankton activity, with lower leucine incorporation rates corresponding to layers where patches of Antarctic Intermediate Water were detected. Coast-ocean and surface-depth gradients in bulk prokaryotic abundance and production and assemblage composition were comparable to changes observed in basin-scale studies, pinpointing the CTZs as regions of strong variability in microbial diversity and metabolism. © Inter-Research 2007 Fieldwork was supported by the CONAFRICA (CTM2004-02319) and RODA (CTM 2004- 06842-C03/MAR) projects. This is a ...